1992
DOI: 10.1016/s0723-2020(11)80130-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Complex and Core Lipids within New Hyperthermophilic Members of the Archaea Domain

Abstract: SummaryCore and complex lipids of several new hyperthermophilic archaeal isolates were analyzed. The organisms belong to the Sulfolobales,Archaeoglobus, Pyrobaculum, and Methanococcus. A detailed structural investigation of complex lipids of Pyrobaculum species is reported. The different lipid structures are of help for a rapid and simple phylogenetic classification of the new isolates. They are in agreement with the classification based on other features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Sprott et al 12 detected ions corresponding to all types of components in total polar lipid extracts using fast atom bombardment mass spectrometry (FABMS) from several archaeal thermophiles, to show the presence of minor amount of diether lipids in Sulfolobus acidocaldarius adding to the ether lipids reported by Gulik et al 9 and Trincone et al 8 High‐performance liquid chromatographic (HPLC) analyses were carried out for tetraethers obtained by acid hydrolysis of complex lipids from Desulfurolobus ambivalence and Sulfolobus solfataricus 13. The results revealed that the cyclic components of tetraether fractions, in particular in the case of D. ambivalens , showed significant differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sprott et al 12 detected ions corresponding to all types of components in total polar lipid extracts using fast atom bombardment mass spectrometry (FABMS) from several archaeal thermophiles, to show the presence of minor amount of diether lipids in Sulfolobus acidocaldarius adding to the ether lipids reported by Gulik et al 9 and Trincone et al 8 High‐performance liquid chromatographic (HPLC) analyses were carried out for tetraethers obtained by acid hydrolysis of complex lipids from Desulfurolobus ambivalence and Sulfolobus solfataricus 13. The results revealed that the cyclic components of tetraether fractions, in particular in the case of D. ambivalens , showed significant differences.…”
Section: Introductionmentioning
confidence: 99%
“…The complex ether lipids of Sulfolobus contain phospholipids, glycolipids, phosphoglycolipids and glycolipid sulfate 8. These polar groups contribute significantly to the physical polymorphism of the tetraethers 9.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the growth temperature, certain thermophilic archaea are capable of controlling membrane fluidity by altering the number of cyclopentane rings from 0 to 8 in the caldarchaeol lipid chains (11). The macrocyclic archaeol lipid has so far been found only in M. jannaschii (6) and Methanococcus igneus (12).…”
mentioning
confidence: 99%
“…This temperature is also consistent with the temperature limit observed for methanogenesis using enrichment culture at Yellowstone National Park, which was 72°C (Zeikus et al, 1980). Polar iGDGT-0 at higher temperatures, albeit at low relative abundance, could derive from a large number of microorganisms, but may possibly be connected with the presence of Archaeoglobus , which is known to produce iGDGT-0 as the only iGDGT (Trincone et al, 1992). Several studies have documented Archaeoglobus in Great Basin hot springs at temperatures up to 85°C (Costa et al, 2009; Dodsworth et al, 2011b; Cole et al, 2013; Peacock et al, 2013).…”
Section: Discussionmentioning
confidence: 99%